'Inside-out', back-to-front: a model for clinical population genetic screening. Issue 7 (July 1993) - Shickle, D; Harvey, I
Abstract : Developments in DNA technology have resulted in a dramatic increase in the number of genes identified. With the localisation of a gene it is possible to devise procedures suitable for mass carrier screening programmes. Until recently mass carrier screening was only possible for a limited number of disorders, for example, Tay-Sachs disease and haemoglobinopathies. Counselling possible carriers was based on estimations of risk. The momentum towards mass carrier screening is likely to be increased by gene therapy. Carrier screening for cystic fibrosis alone will have dramatic implications for genetic service provision as 4 to 5% of the UK population carry the CF gene. The potential for genetic screening of multifactorial diseases, for example, cancers, should also be considered. The existing organisation of genetic services is likely to be inadequate. A new specialty of clinical population genetics is required. A model is proposed of clinical population genetic screening programmes, organised under a 'common umbrella' led by a public health physician, while screening and follow up will remain the responsibility of the appropriate clinician.